D-Qalami: Guess-and-action cards, Islamic educational media of health and environmental aspects for students of Al-Qur'an Learning Center - Panji Nur Fitri Yanto; Trisna Avi Listyaningrum; Dedek Ajeng Okta Triana; Cut Zahiya Listy Humaira; Muhammad Fikri Rayendra; Nur Fatimah; Widodo Hariyono (Community Empowerment, 2021)
It is crucial that learning media be developed alongside the development of a more modern era. This concerns not just classroom learning but unorthodox forms of education, as is practiced in the Al-Qur'an Learning Center (TPA). Currently, TPA is just a place to learn to read the Qur'an with simple teaching and learning techniques and religion-related media. The existing game cards revolve around Islam, among others. On the other hand, thematic learning media products related to health and environmental issues that align with Islamic values were initiated. A 4D model (Define, Design, Development, and Dissemination) of Research and Development (RnD) was used to create D-Qalami: Guess the Meaning and Action Card, an Islamic educational media for the health and environmental aspects of the Santri TPA (abbreviated as D-Qalami). It comes as unique, practical, and informative folding cards that make remembering easy. This product presents aspects of personal health in a manner that is in line with Islamic values. D-Qalami is equipped with interesting supporting books and can be studied by various groups and ages, especially children.